Missing pancreatic isthmus during pancreaticoduodenectomy - Knoop, Michael (J Surg Case Rep, 2015)
Pancreatic malformations usually represent a surgical challenge, however, depending on the anatomical location even complex procedures such as pancreatic head resection may be facilitated. In a 78-year-old-woman the unique observation of a missing pancreatic isthmus was made during pylorus-preserving pancreaticoduodenectomy for pancreatic ductal adenocarcinoma. Resection of the pancreatic head could be performed without the usual cross-section at the isthmus, the pancreatic remnant was drained by pancreaticogastrostomy. Complete agenesis of the dorsal pancreas with missing neck, body and tail of the pancreas has been shown to be associated with malignant pancreatic tumors, as demonstrated in this case of partial agenesis (missing isthmus) of the dorsal pancreas. The missing pancreatic isthmus is a unique, not yet described finding during pancreatic exploration for tumor resection. In the absence of previous abdominal trauma, a partial agenesis of the dorsal pancreas could explain this malformation.